2001
DOI: 10.4049/jimmunol.166.10.6341
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Selective Nonpeptide Antagonist of the Anaphylatoxin C3a Receptor That Demonstrates Antiinflammatory Activity in Animal Models

Abstract: The anaphylatoxin C3a is a potent chemotactic peptide and inflammatory mediator released during complement activation which binds to and activates a G-protein-coupled receptor. Molecular cloning of the C3aR has facilitated studies to identify nonpeptide antagonists of the C3aR. A chemical lead that selectively inhibited the C3aR in a high throughput screen was identified and chemically optimized. The resulting antagonist, N(2)-[(2,2-diphenylethoxy)acetyl]-L-arginine (SB 290157), functioned as a competitive ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
195
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(203 citation statements)
references
References 38 publications
8
195
0
Order By: Relevance
“…This compound, N(2)-[(2,2-diphenylethoxy)acetyl]-L-arginine, antagonised C3a-induced calcium mobilisation, smooth muscle contraction and attenuated paw oedema in a rat model of adjuvant-induced arthritis (Ames et al, 2001). Given the in vivo anti-inflammatory activities reported, and because to date the effects of this C3aRA have only been reported in one in vitro study (Mollnes et al, 2002), we decided to investigate its pharmacology in more detail and compare its actions with a small molecule C5aRA, which has been well characterised (Strachan et al, 2000;Arumugam et al, 2002;Woodruff et al, 2002;.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…This compound, N(2)-[(2,2-diphenylethoxy)acetyl]-L-arginine, antagonised C3a-induced calcium mobilisation, smooth muscle contraction and attenuated paw oedema in a rat model of adjuvant-induced arthritis (Ames et al, 2001). Given the in vivo anti-inflammatory activities reported, and because to date the effects of this C3aRA have only been reported in one in vitro study (Mollnes et al, 2002), we decided to investigate its pharmacology in more detail and compare its actions with a small molecule C5aRA, which has been well characterised (Strachan et al, 2000;Arumugam et al, 2002;Woodruff et al, 2002;.…”
Section: Discussionmentioning
confidence: 95%
“…A previous study (Ames et al, 2001) reported the discovery of a nonpeptidic C3aRA with high affinity for the human C3aR. This compound, N(2)-[(2,2-diphenylethoxy)acetyl]-L-arginine, antagonised C3a-induced calcium mobilisation, smooth muscle contraction and attenuated paw oedema in a rat model of adjuvant-induced arthritis (Ames et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Currently, C3a is 20 commercially produced in relatively low yields by biological means (recombinant expression or purification from plasma) 3, 4 resulting in a market value of approximately US$ 5000 per mg of protein. In addition, these approaches often require protein purification tags and additional steps for their removal and suffer 25 from the inherent lability of C3a in biological fluids. C3a is rapidly inactivated within seconds by carboxypeptidase-mediated cleavage of a single C-terminal arginine residue (Arg 77 ).…”
mentioning
confidence: 99%